Ants respond more strongly to grazing than changes in shrub cover. (2nd March 2018) - Radnan, Gabriella N.; Eldridge, David J.
Abstract: Increases in the cover or density of woody plants (encroachment) and overgrazing by European livestock are 2 major drivers of ecosystem structure and function in drylands and are often associated with land degradation. Although the effects of encroachment and overgrazing on vascular plants are relatively well known, little is known about their effects on arthropods such as ants. We examined ant community composition at sites ranging in shrub cover in a wooded dryland in eastern Australia, testing the notion that increasing shrub cover and grazing intensity would alter ant assemblages and functional group composition. We used ants because they are abundant, diverse, and respond to small‐scale environmental changes. Increasing shrub cover had no effect on ant richness, diversity, or evenness but increased the abundance of Subordinate Camponotini. Larger shrubs tended to have greater ant richness, and abundance of Cold Climate Specialists, but fewer Generalized Myrmicinae and Hot Climate Specialists. More intense grazing was associated with greater ant richness, diversity, and evenness; a greater abundance of Hot Climate Specialists and Dominant Dolichoridae; and lower abundance of Subordinate Camponotini. Our study indicates that changes in grazing intensity had stronger effects on ant richness than any increase in shrub cover. The effects of grazing likely resulted from changes in soil surface complexity such as barer ground associated with grazing‐induced degradation.